Capacidad de humectación de soluciones irrigantes del tratamiento de conductos radiculares. In vitro - Anglas Machacuay, Abel (2016)
Objective: the objective of this study was to determine and analyze the wettability of irrigating solutions of root canal treatment in bovine tooth dentin surface. Materials and method: For the study were prepared 15 acrylic blocks :40 mm x 30 mm x 8 mm wherein a surface exposed tooth dentin of bovine tissue. There were used as test irrigants: 5,25% sodium hypochlorite solution, 0,12% chlorhexidine gluconate, water saturated with calcium hydroxide and sodium chloride solution 9/1000. On dentin surface was deposited a calibrated drop of irrigating solution, this sessile drop contact with dentin surface showed many forms which were photographed to measure them with a conveyor provided the angle (contact angle). Results showed that Chlorhexidine Gluconate 0,12 %, established a contact angle with an average of 41.33°, followed by water saturated with calcium hydroxide (43.23º), sodium hypochlorite 5,25 % (61.17º) and saline 9/1000 with 61.43º.Conclusion: It is concluded that chlorhexidine and water saturated with calcium hydroxide are irrigants with better ability to humectancy on bovine dentin. Unexpected result because of the molecular characteristics it was believed to sodium hypochlorite have a better ability to humectancy.